PENGARUH ROA, LEVERAGE, DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE PADA PERUSAHAAN PERTAMBANGAN ERA JOKOWI – JK - Gumono, Clarissa Octa (Media Akuntansi dan Perpajakan Indonesia, 2021)
Taxes are income for the state which are useful for financingstate activities and operations. Unfortunately, taxes are not profitable forcompanies. Taxes can decrease its profit. This situation triggers the companyto take action related to agency theory. This actions taken by managingtax financing so that it can be effective and efficient without violatingexisting regulations. That actions called tax avoidance. Tax avoidance takesadvantages of the grey area in the tax regulations so that the actions takenlegally. Tax avoidance in this study is used as the dependent variable bycalculating the cash effective tax rate (cash ETR). Independent variable inthis study are return on assets (ROA), leverage, and capital intensity. Theexistence of these variables are used to support the purpose of this study.The purpose of this study is to determine the influence of ROA, Leverageand Capital intensity on tax avoidance. The data used are from the financialreports and annual reports of mining sector companies listed in IndonesiaStock Exchange during the Jokowi - JK’s era.